Pengaruh pupuk NPK dan kompos terhadap pertumbuhan semai gmelina (Gmelina arborea Roxb.) pada media tanaha bekas tambang emas (tailing) - Basuki Wasis; Nuri Fathia (Institut Pertanian Bogor, 2010)
Mining activities could adversely affect the environment if the waste it generates is not processed properly. Negative impacts include disruption of natural ecosystems in the form of changes in soil structure resulting morphology and physical conditions, chemical and biological soil becomes worse. Tailings are mineralmineral/ logam-logam composite weight from mining activities, has a sandy texture. Planting crops gmelina (Gmelina arborea Roxb.) On the media tailings with the addition of NPK fertilizer and composted manure is expected to improve the physical properties, chemical and biological soil tailings as a medium for plant growth in land revegetation efforts. Experimental design used in this study was factorial design with two factors. The first factor is fertilizer NPK with 4 level and the second factor is the compost with 4 level. The interaction between NPK fertilizer and compost that give real effect on the growth of both high and diameter gmelina. So that the resulting growth in both fertilizer interaction produces a real growth. A2B3 combination treatment (NPK 10 grams to 30 grams of compost) to give the most obvious influence with the highest growth in response to the control that is 7.56 em 75.08%). In the interaction treatment A3BO (NPK fertilizer with compost 15 grams 0 grams) shows the percentage growth in value of the diameter of the supreme control of 0.0575 em 22.716%).",